ANALISIS KONTEN DIGITAL MARKETING BERBASIS SOCIAL MEDIA MARKETING MENGGUNAKAN USER EXPERIENCE QUESTIONARE - Komang Tri Werthi; Ketut Queena Freedlina (Jurnal Bisnis Darmajaya, 2020)
Bali is one of the biggest foreign exchange earners in the Indonesian economy in tourism. Not all tourist attractions in Bali are fully publicized and promoted. If is maximized it can increase tourist visits to Bali. One of the digital marketing media is social media. Through social media tourists can get information about the location, what is offered, a review of the tourist attraction, and so on. This study analyzes the value equity, relationship equity, and brand equity in the tourism system of Lake Buyan in Bali Province on social media marketing. In the end, it will produce social media marketing based marketing strategies. The method used is the creation of social media marketing as a means of publication information, and promotion of Lake Buyan attractions. then assed by using UEQ (user experience questionnare). Lake Buyan’s UEQ social media Instagram results have a lack of efficiency (Value Equity) and novelty (Brand Equity) that are poorly organized, not yet creative and innovative. The highest value of Relationship Equity was 1.934 1.868 excellent dark green color. This shows that Lake Buyan's social media is more organized, interesting, creative, understandable in terms of followers. Keywords — Customer equity, social media marketing